IDENTIFICATION OF PHYSICAL OCEANOGRAPHIC PARAMETERS AND MIXING TYPES AT THE TRANSITIONAL SEASON I IN THE ESTUARY OF AIR MANNA REGENCY SOUTH BENGKULU - Supiyati, Supiyati; Sari, Devi Permata; Ekawita, Riska; Johan, Septi; Sudirman, Sudirman (Spektra: Jurnal Fisika dan Aplikasinya, 2023)
The recent increase in community activity in the Air Manna Estuary of the South Bengkulu regency, will affect the physical condition of the estuary. Therefore, this research were to determine of the physical oceanographic parameters such as temperature, salinity, current velocity, tidal and the mixing type in the Air Manna estuary, South Bengkulu Regency at the transitional season I. The method used is the measurement of field data directly during high tide and low tide conditions as well as descriptive and quantitative data analysis. The results showed that the characteristics of the physical oceanographic pharameters in the Air Manna Estuary were influenced by tidal condition. The highest current speed at the mouth of the estuary is 2.6 m/s at low tide and 2.2 m/s at high tide, with the highest temperature in the upstream estuary of 27.49oC towards the sea during high tide conditions. The low salinity in the middle of the estuary of 0.99 ppt increases towards the sea with a relatively smaller distribution of salinity at low tide.The mixing type in the Air Manna Estuary is the Salt wedge estuary which has a well-certified mixing pattern, with an estuary number of 0.00019.